The pedagogical analysis of educational process on physical training in legal higher education Institution. - Popichev M.I (Kharkov National Pedagogical University, 2010)
Materials of research of a psychophysiological state of health of students of the Crimean legal institute of National legal academy of Ukraine of Yaroslav the Wise name are considered. The organization of educational process on physical training taking into account specific features of human body is analysed. In experiment take place 637 students in the middle age 18 years. It is established that the psychophysiological condition of students has the specific features. It is estimated that it plays a dominant role in the general system of physical preparation taking into account each engaged. It is proved that the cores to criteria of the organization of process of training are the account of level of physical readiness and a psychological condition.